Model Analysis for Grapes under Weather Conditions Using Various Statistical Study Approach - Eswari , A.; Saravanakumar, S. (Emerging Issues in Agricultural Sciences Vol. 6, 2023)
Grape is the most important crop, and it is planted in nearly every country on the planet. Tamil Nadu is the major producer of grape in Theni district, followed by Dindigul and Coimbatore; hence this research is focused on the Theni district. Muscat Humbug is the popular variety which gives better yield than other varieties. This study was carried out on Muscat Humbug variety. In this chapter, statistical models for different techniques are discussed. A climatic yield prediction model for grape is developed and analytically solved using statistical techniques. The model enables the evaluation of key mechanisms to go through and the effects of various agricultural practises on the amount and quality of the output. In this study, recent key developments in the modelling of prediction of yield and disease incidence are reviewed. These modelled mostly correlated with climatic factors. Because, climate has a direct influence on crop development and the final yield. This chapter is dedicated to the modelling of yield prediction for grape by different statistical methods and numerical solutions. Detailed maps and charge balances are combined with a model for the reaction mechanism in the grape. It is important that theoretical models are developed to reduce the burden on laboratory-based testing and accelerate the development of practical systems.